COMPLIMENT AS AN INTEGRAL COMPONENT OF SPEECH ETIQUETTE IN ENGLISH AND UZBEK LANGUAGE - Isakova Feruza Muxamadinovna, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2026)
Abstract: Compliments constitute one of the most significant expressive speech acts in human communication. As an integral component of speech etiquette, compliments contribute to maintaining social harmony, reinforcing interpersonal relationships, and reflecting cultural values. This article provides a comparative analysis of compliments in English and Uzbek linguistic and cultural contexts. Drawing on pragmatic, sociolinguistic, and intercultural frameworks, the study examines structural patterns, communicative functions, response strategies, and sociocultural constraints governing the use of compliments. The findings reveal that while compliments perform universal social functions in both languages, their realization is deeply influenced by cultural norms such as individualism, collectivism, modesty, and power distance. The study emphasizes the importance of pragmatic competence in cross-cultural communication and foreign language teaching.